Hukum di Era Globalisasi dan Pengaruhnya Terhadap Pembangunan Ekonomi dan Fungsi Konservasi Lingkungan - Fitria Wilandari, Devi (Program Studi Hukum Universitas Pamulang, 2024)
Economic globalization raises a huge effect on a country's legal system, because theglobalization of the economy led to globalization of law. The globalization of law isbased not only international agreement among nations, but also understanding the legal tradition and culture between west and east. However, the role of law in economic development and natural resource management (SDA) in the era ofglobalization and modernization is still debated. The study in this paper describe:impact of globalization on economic development and its impact on the environmentin Indonesia, an effort that can be done in order to develop the Indonesian legalsystem to deal with the global economy that tends to disadvantage the position ofIndonesia as well as efforts to maintain the natural resource conservation andenvironmental functions, the concept of legal system development based onsubstantial values of Pancasila and UUD 1945, as the solution to Indonesia in theface of the global economic system as well as conserve natural resources andenvironmental functions.The results explain that: first, the impact of globalization led to the country's sovereignty be neglected, weakened the state power along with the subjugation of the country at international institutions, such as the WTO with its free market agenda, forcing the state to not protect the basic rights of citizens against natural resources and environment; second, Efforts that can be done in order to develop the nationallegal system that is setting the economy law must consider the legal interests of thevarious relevant sectors in a balanced way; third, the concept of the Indonesian legal system should be developed now that the concept of legal development that is based on substantial values of Pancasila and UUD 1945, namely a legal system with theadvanced principle of nationality or kinship, which gives more emphasis on the ruleof morality of the rule of law.